Wire retiming as fixpoint computation. - Chuan Lin
In system-on-chips (SOCs), a nonnegligible part of operation time is spent on global wires with long delays. Retiming-that is moving flip-flops in a circuit without changing its functionality-can be explored to pipeline long interconnect wires in SOC designs. The problem of retiming over a netlist of macro-blocks, where the internal structures may not be changed and flip-flops may not be inserted on some wire segments is called the wire retiming problem. In this paper, we formulate the constraints of the wire retiming problem as a fixpoint computation and use an iterative algorithm to solve it. Experimental results show that this approach is multiple orders more efficient than the previous one.
Keywords: Circuit modeling; Circuit optimization; Constraint formulation; Fixpoint computation; Interconnects; Iterative algorithm; Problem solving; System-on-chip.; Wire retiming